Highly Photoluminescent and Environmentally Stable Perovskite Nanocrystals Templated in Thin Self‐Assembled Block Copolymer Films. (13th March 2019) - Han, Hyowon; Jeong, Beomjin; Park, Tae Hyun; Cha, Wonhee; Cho, Suk Man; Kim, Yeongsik; Kim, Hong Hee; Kim, Dongho; Ryu, Do Yeol; Choi, Won Kook; Park, Cheolmin
Abstract: Ordered nanostructured crystals of thin organic–inorganic metal halide perovskites (OIHPs) are of great interest to researchers because of the dimensional‐dependence of their photoelectronic properties for developing OIHPs with novel properties. Top‐down routes such as nanoimprinting and electron beam lithography are extensively used for nanopatterning OIHPs, while bottom‐up approaches are seldom used. Herein, developed is a simple and robust route, involving the controlled crystallization of the OIHPs templated with a self‐assembled block copolymer (BCP), for fabricating nanopatterned OIHP films with various shapes and nanodomain sizes. When the precursor solution consisting of methylammonium lead halide (MAPbX3, X = Br −, I − ) perovskite and poly(styrene)‐ block ‐poly(2‐vinylpyridine) (PS‐ b ‐P2VP) is spin‐coated on the substrate, a nanostructured BCP is developed by microphase separation. Spontaneous crystallization of the precursor ions preferentially coordinated with the P2VP domains yields ordered nanocrystals with various nanostructures (cylinders, lamellae, and cylindrical mesh) with controlled domain size (≈40–72 nm). The nanopatterned OIHPs show significantly enhanced photoluminescence (PL) with high resistance to both humidity and heat due to geometrically confining OIHPs in and passivation with the P2VP chains. The self‐assembled OIHP films with high PL performance provide a facile control of color coordinates by color conversion layers in blue‐emitting devices for cool‐white emission. Abstract : A bottom‐up route for fabricating nanostructured organic–inorganic halide perovskite films is developed by controlled crystallization of the perovskites templated with a self‐assembled block copolymer. Nanopatterned perovskite films with various shapes and nanodomain sizes show excellent photoluminescence with significantly enhanced heat and humidity resistance, making them suitable as color conversion layers for cool‐white emission.